The Contribution of Peer Social Support to Psychological Well-Being among Overseas Students - Wulandari; Komarudin; Hallare, Syrell M.; Loyola, Allysssa DL. (The Indonesian Institute of Science and Technology Research, 2024)
Overseas students are students who receive higher education and live far from their place of birth, parents, and relatives and must face academic and psychological challenges during their education. The many difficulties and demands expose overseas students to psychological disorders that impact their psychological well-being. As a result, overseas students require social support from those around them; social support is one of the fact factors affecting call well-being. Peer social support is one of several components of social support. The study aims to determine the role of peer social support in the psychological well-being of overseas students in Yogyakarta. Data was collected using a peer social support scale and a Likert scale model for psychological well-being. One hundred seven (170) overseas students in Yogyakarta between 18 and 21 years old participated. According to the findings of this study, there is a significant positive relationship between peer social support and psychological well-being. The effective contribution in this study is 39.8 percent, and the correlation coefficient is 0.631. In this study, the significance level was 0.005 < 0.05.